Pengaruh Model Pembelajaran dan Gaya Belajar terhadap Hasil Belajar Peserta Didik - Netti Herawati; Ulben Syarifuddin; Halimah Husain (Program Pasca Sarjana UNM, 2022)
This study is a quasi-experimental research that aims to discover the effect of learning models and learning styles on learning outcomes of grade XI students of MIPA at SMAN 1 Kalukku. The independent variables in this study were the learning models and learning styles of students, and the dependent variable was the learning outcomes on Colloid System subject. The population of the study were students of grade XI MIPA at SMAN 1 Kalukku with the total of 7 classes. The sample of the study was determined by using random sampling technique consisted of 2 classes, namely Class XI MIPA 1 (Class A) and XI MIPA 3 (Class B). The research design employed factorial. The research data was obtained by giving a test of learning outcomes on Colloid System material in the form of a post-test consisted of 25 multiple-choice questions. The data analysis techniques used descriptive and inferential statistical analysis. Hypothesis testing was conducted with the F test (ANOVA) at a significance level of α = 0.05. The results of hypothesis testing with the F test prove that there is an influence of learning models on learning outcomes, there is an influence of learning styles on learning outcomes, and there is an influence of interaction between learning models and learning styles on learning outcomes of grade XI students of MIPA at SMAN 1 Kalukku, studies on Colloid System subject.